Drip irrigation and Fertigation improves yield and water productivity of summer sesame: Drip irrigation and Fertigation improves yield and water productivity of summer sesame - K AVIL KUMAR; T L NEELIMA; V RAMULU (Journal of Oilseeds Research, 2023)
A field experiment was conducted during summer on sesame (var. Swetha) at College Farm, Rajendranagar, Hyderabad with two irrigation levels (0.8 and 1.0 Epan), two fertigaiton levels of 75% and 100% recommended dose Nitrogen and Potassium (RD of N & K) and two dosage schedules (Equal and differential) in Randomized Block Design. The results revealed that the 100% RD of N & K in differential dosages recorded higher yield (1011 kg /ha) at 1.0 Epan and highest water productivity (2.4 kg mm-1) was observed in irrigation at 0.8 Epan with fertigation of 100% RD N&K in differential dosages.